Na-modified Zn-coated MFI molecular sieve monatomic catalyst as well as preparation method and application thereof
By using Na-modified Zn@MFI single-atom molecular sieve catalyst in the ethanol dehydrogenation reaction, the problems of high cost and low selectivity of ethanol dehydrogenation catalysts in the prior art are solved, and efficient and economical acetaldehyde production is achieved.
Patent Information
- Application Number
- CN202411811912.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, ethanol dehydrogenation catalysts have problems of high cost and low selectivity, making it difficult to achieve economical and efficient acetaldehyde production.
Through a one-step hydrothermal synthesis and crystallization method, the Na-modified Zn@MFI single-atom molecular sieve catalyst was constructed using the strategies of ligand protection and Na modification, which achieved the single-atom dispersion of Zn and the alkali-center regulation of Na.
It has achieved 100% Zn atom utilization rate, nearly 100% acetaldehyde selectivity and reaction stability of more than 300 hours, reducing catalyst costs and improving industrialization prospects.
Smart Images

Figure CN119608226A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and specifically relates to a Na-modified Zn@MFI single-atom molecular sieve catalyst, a preparation method thereof, and an application in the non-oxidative dehydrogenation of ethanol. Specifically, the coordination structure of Zn and the acidity and alkalinity of the catalyst are adjusted by using a ligand protection and Na modification strategy, so as to achieve the conversion of ethanol into acetaldehyde with high activity, high selectivity and high stability. Background Art
[0002] As an important platform compound, acetaldehyde can be converted into a series of chemical products such as acetone, butanol, crotonaldehyde, sorbitol, butadiene and pentaerythritol through catalytic conversion, and has high industrial application value [ACS Catal., 13 (2023) 11291-11304.]. The ethanol dehydrogenation process plays a vital role as an intermediate step in the conversion of ethanol into high value-added products. In recent decades, the production of bioethanol has been continuously upgraded, and the use of biomass (such as cassava and cellulose) as raw materials has made the process more attractive. [Resources Chemicals and Materials, 2 (2023) 189-207.] In addition, ethanol dehydrogenation is a crucial step in the ethanol-liquid organic hydrogen carrier circulation system. Compared with commercially available copper-based catalysts, precious metal catalysts show higher activity in ethanol dehydrogenation reactions, but their high cost limits their wide application [Chinese Journal of Catalysis, 49 (2023) 91-101.]. Therefore, there is an urgent need to develop low-cost, efficient and highly selective ethanol dehydrogenation catalysts.
[0003] Single-atom catalysts can reduce catalyst costs and achieve maximum utilization efficiency of metals. Precious metal (Au, Ag, Pt, etc.) single-atom catalysts show excellent catalytic performance in ethanol dehydrogenation reactions. However, single-atom catalysts based on cheap metals as active centers have rarely been reported in ethanol dehydrogenation reactions. Summary of the invention
[0004] The purpose of the present invention is to provide a Na-modified Zn@MFI single-atom molecular sieve catalyst, a preparation method thereof and an application in the non-oxidative dehydrogenation of ethanol. A one-step hydrothermal synthesis crystallization method is adopted to construct a Zn single-atom molecular sieve catalyst through ligand protection and base center regulation strategy, wherein Zn is dispersed in the molecular sieve in a single-atom state. The catalyst can achieve 100% Zn atom utilization, nearly 100% acetaldehyde selectivity and 300 hours of reaction stability.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] On the one hand, the present invention provides a Na-modified Zn@MFI molecular sieve single-atom catalyst, wherein the catalyst is represented by the formula Zn-Na@MFI, wherein Zn and Na are active components, and an MFI molecular sieve carrier is provided, Zn is dispersed in the MFI molecular sieve carrier in the form of a single atom, and the loading amounts of the active components Zn and Na elements in the catalyst are 0.1-1wt% and 0.2-2wt%, respectively.
[0007] In the above technical solution, further, the loading amount of Zn element in the catalyst is 0.01-0.2wt%; the loading amount of Na element in the catalyst is 0.02-0.5wt%.
[0008] Another aspect of the present invention provides a method for preparing the above-mentioned catalyst, the method comprising the following steps:
[0009] (1) mixing a silicon source, a template, a ligand protective agent, a sodium source, a zinc source and water, controlling the pH value to be 9-13, and stirring for 1-5 hours to obtain a gel;
[0010] (2) subjecting the gel obtained in step (1) to a hydrothermal crystallization reaction;
[0011] (3) After the hydrothermal crystallization is completed, centrifugation is performed, and drying is performed under vacuum conditions, followed by reduction calcination in a hydrogen atmosphere. The reduction calcination temperature is 350-750° C. and the calcination time is 2-6 h to obtain the catalyst.
[0012] In the above technical solution, further, in step (1), the molar ratio of the silicon source, template, ligand protective agent, sodium source, zinc source and water is 1:2-5:0.02-0.1:0.001-0.02:0.001-0.01:20-50.
[0013] In the above technical solution, further, in step (1), the silicon source is one or both of ethyl orthosilicate and silica sol;
[0014] The sodium source is one or more of sodium nitrate, sodium hydroxide, sodium chloride, sodium benzoate, and sodium carbonate;
[0015] The zinc source is one or more of zinc nitrate, zinc chloride, zinc acetylacetonate and zinc acetate;
[0016] The template agent is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide;
[0017] The ligand protecting agent is one or more of ethylenediamine, ethylenediaminetetraacetic acid and dopamine.
[0018] In the above technical solution, further, in step (2), the hydrothermal crystallization temperature is 100-200°C and the time is 36-120h, preferably the hydrothermal crystallization temperature is 120-180°C and the time is 60-90h.
[0019] In the above technical solution, further, in step (3), the drying temperature is 50-120°C, preferably 80-120°C;
[0020] The hydrogen flow rate is 10-100 ml / min, preferably 30-50 ml / min;
[0021] The reduction roasting temperature is 400-500° C., and the roasting time is 3-5 hours.
[0022] The present invention also provides an application of the above catalyst in the non-oxidative dehydrogenation of ethanol to acetaldehyde, wherein the reaction is carried out in a fixed bed reactor, the ethanol feed flow rate is 0.005-1 ml / min, preferably 0.01-0.2 ml / min, and the reaction mass space velocity is WHSV=0.5-10 h -1 , preferably WHSV = 1-3h -1 , using at least one of argon, nitrogen and helium as carrier gas, the carrier gas flow rate is 40-200 mL / min, and the reaction temperature is 150-400°C, preferably 250-350°C.
[0023] The beneficial effects of the present invention are:
[0024] (1) Zn is dispersed in the molecular sieve in a single-atom state, achieving 100% atomic utilization efficiency.
[0025] (2) Using low-cost metal Zn as the active component is more economical and has a more prominent industrial prospect than traditional precious metal (such as Au, Ag) catalysts.
[0026] (3) By introducing the base center Na, 100% selectivity for acetaldehyde was achieved.
[0027] (4) The Zn species was stabilized in the molecular sieve through a ligand protection strategy, achieving reaction stability that could last for more than 300 hours in a single run. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The XRD characterization results of the catalysts prepared in Examples 1-4;
[0029] Figure 2 The N2 physical adsorption characterization results of the catalyst prepared in Example 1;
[0030] Figure 3The dispersion state of the active components of the catalyst prepared in Example 1 before and after the reaction;
[0031] Figure 4 The following are the results of investigating the stability of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0032] The following examples are further described in detail. The following examples may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0033] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0034] Example 1
[0035] The Zn-Na@MFI molecular sieve single atom catalyst was prepared by a one-step hydrothermal synthesis crystallization method, which includes the following steps:
[0036] (1) A silicon source (ethyl orthosilicate), a template (tetrapropylammonium hydroxide), a ligand protective agent (ethylenediaminetetraacetic acid), a sodium source (sodium hydroxide), zinc acetate and water are mixed in a molar ratio of 1:2.3:0.1:0.002:0.001:40, the pH value is adjusted to about 9, and a gel is obtained after stirring for 3 hours;
[0037] (2) transferring the obtained gel to a hydrothermal reactor and crystallizing it in an oven at 170°C for 72 h;
[0038] (3) After the hydrothermal crystallization was completed, the white gel was obtained by centrifugation three times, which was then vacuum dried at 120°C and reduced and calcined at 550°C for 4 h in a hydrogen atmosphere (flow rate of 30 ml / min) to obtain a single atom catalyst, which was recorded as Zn1-Na2@MFI.
[0039] Embodiment 2-4
[0040] Preparation of single-atom Zn-Na@MFI molecular sieve catalysts with different zinc loadings
[0041] The preparation process of Examples 2-4 is similar to that of Example 1, except that the content ratio of zinc to silicon is different. The molar ratio of silicon to zinc is 1:0.002, 1:0.005 and 1:0.01, respectively. The obtained catalysts are named Zn2-Na2@MFI, Zn5-Na2@MFI, Zn 10 -Na2@MFI.
[0042] The ICP results of Zn and Na in Zn-Na@MFI catalysts with different zinc loadings are shown in Table 1.
[0043] Table 1 ICP results of Zn and Na in Zn-Na@MFI catalysts with different zinc loadings
[0044] Example catalyst Zinc loading (%) Sodium loading (%) 1 <![CDATA[Zn1-Na2@MFI]]> 0.1 0.2 2 <![CDATA[Zn2-Na2@MFI]]> 0.2 0.2 3 <![CDATA[Zn5-Na2@MFI]]> 0.5 0.2 4 <![CDATA[Zn 10 -Na2@MFI]]> 1 0.2
[0045] ICP results showed that the zinc loading in Zn-Na@MFI catalyst was in the range of 0.1%-1%.
[0046] Embodiment 5-7
[0047] Preparation of single-atom Zn-Na@MFI molecular sieve catalysts with different sodium contents
[0048] The preparation process of Examples 5-7 is similar to that of Example 1, except that the content ratio of sodium to silicon is different. The molar ratio of silicon to sodium is 1:0.004, 1:0.006 and 1:0.01, respectively. They are named Zn1-Na4@MFI, Zn1-Na6@MFI, Zn1-Na 10 @MFI.
[0049] ICP results of Zn and Na in Zn-Na@MFI catalysts with different sodium loadings.
[0050] Table 2 ICP results of Zn and Na in Zn-Na@MFI catalysts with different sodium loadings
[0051] Example catalyst Zinc loading (%) Sodium loading (%) 1 <![CDATA[Zn1-Na2@MFI]]> 0.1 0.2 5 <![CDATA[Zn1-Na4@MFI]]> 0.1 0.4 6 <![CDATA[Zn1-Na 10 @MFI]]> 0.1 1 7 <![CDATA[Zn1-Na 20 @MFI]]> 0.1 2
[0052] ICP results showed that the sodium content in Zn-Na@MFI catalyst was in the range of 0.2%-2%.
[0053] Embodiment 8-11
[0054] Preparation of single-atom Zn-Na@MFI molecular sieve catalysts at different calcination temperatures:
[0055] The preparation process of Examples 8-11 is similar to that of Example 1, except that the calcination temperatures are 350°C, 450°C, 650°C, and 750°C, respectively.
[0056] Comparative Example 1
[0057] The preparation of single-atom Zn@MFI molecular sieve catalyst includes the following steps:
[0058] (1) A silicon source (ethyl orthosilicate), a template (tetrapropylammonium hydroxide), a ligand protective agent (ethylenediaminetetraacetic acid), zinc acetate and water were mixed in a molar ratio of 1:2.3:0.1:0.001:40, the pH value was adjusted to about 9, and a gel was obtained after stirring for 3 hours;
[0059] (2) transferring the obtained gel to a hydrothermal reactor and crystallizing it in an oven at 170°C for 72 h;
[0060] (3) After the hydrothermal crystallization was completed, the white gel was centrifuged three times and then dried at 120°C in vacuum. It was then reduced and calcined at 550°C for 4 h in a hydrogen atmosphere (flow rate of 30 ml / min) to obtain the Zn@MFI single atom catalyst.
[0061] Comparative Example 2
[0062] Nano Zn nano -The preparation of Na@MFI molecular sieve catalyst includes the following steps:
[0063] (1) A silicon source (ethyl orthosilicate), a template (tetrapropylammonium hydroxide), zinc acetate and water were mixed in a molar ratio of 1:2.3:0.001:40, the pH value was adjusted to about 9, and the gel was obtained after stirring for 3 hours;
[0064] (2) transferring the obtained gel to a hydrothermal reactor and crystallizing it in an oven at 170°C for 72 h;
[0065] (3) After the hydrothermal crystallization was completed, the white gel was centrifuged three times and dried in vacuum at 120°C. Then, it was reduced and calcined at 550°C for 4 h in a hydrogen atmosphere (flow rate of 30 ml / min) to obtain nano Zn nano -Na@MFI catalyst.
[0066] Comparative Examples 3-5
[0067] Preparation of single-atom Zn-M@MFI molecular sieve catalysts, where M is other alkali metal centers, Li, K, and Mg.
[0068] The preparation process is similar to that of Example 1, except that the alkali metal sources are lithium hydroxide, potassium hydroxide and magnesium hydroxide, respectively.
[0069] Comparative Example 6
[0070] The same amount of sodium was introduced into the single-atom Zn@MFI molecular sieve catalyst by impregnation method and ion exchange method. Preparation of Na / Zn@MFI catalyst by impregnation method:
[0071] The same amount of sodium as in Example 1 was introduced into the single-atom Zn@MFI molecular sieve catalyst by an impregnation method, specifically: a certain amount of sodium nitrate was dissolved in 1 g of ultrapure water, and after sufficient stirring and dissolution, 1 g of the single-atom Zn@MFI molecular sieve catalyst in Comparative Example 1 was added and impregnated with an equal volume for 12 h. After vacuum drying at 120°C, the catalyst was reduced and calcined at 550°C for 4 h in a hydrogen atmosphere (flow rate of 30 ml / min) to obtain a Na / Zn@MFI catalyst.
[0072] Comparative Example 7
[0073] Preparation of Na-Zn@MFI catalyst by ion exchange method:
[0074] The same amount of sodium as in Example 1 was introduced into the single-atom Zn@MFI molecular sieve catalyst by ion exchange method, specifically: a certain amount of sodium nitrate was dissolved in 100 g of ultrapure water, fully stirred to dissolve, 1 g of the single-atom Zn@MFI molecular sieve catalyst in Comparative Example 1 was added, ion exchange was stirred at room temperature for 12 h, and a solid sample was obtained by filtration. After vacuum drying at 120 ° C, it was reduced and calcined at 550 ° C for 4 h in a hydrogen atmosphere (flow rate of 30 ml / min) to obtain a Na / Zn@MFI catalyst.
[0075] Application Example 1
[0076] Evaluation process of ethanol dehydrogenation to acetaldehyde catalyst: 1 g of the catalyst prepared in Comparative Examples 1-5 and Examples 1-11 was pelletized and loaded into a fixed bed reactor. The ethanol flow rate was 0.02 ml / min. The raw materials were brought into the reactor by pump feeding and nitrogen carrier gas (flow rate of 100 mL / min). The reaction space velocity was WHSV=1 h -1 , the reaction temperature is 300℃.
[0077] Reaction conversion and selectivity calculation method:
[0078] Ethanol conversion rate (%) = (n 反应前的乙醇 -n 反应后剩余乙醇 ) / n 反应前的乙醇 *100%
[0079] Acetaldehyde selectivity (%) = n 产物中乙醛 / (n 反应前的乙醇 -n 反应后剩余乙醇 )*100%
[0080] The performance evaluation results of Zn-Na@MFI catalysts with different zinc loading amounts in Examples 1-4 are shown in Table 3.
[0081] Table 3 Performance evaluation results of Zn-Na@MFI catalysts with different zinc loadings
[0082] Example catalyst Ethanol conversion rate (%) Acetaldehyde selectivity (%) 1 <![CDATA[Zn1-Na2@MFI]]> 36 100 2 <![CDATA[Zn2-Na2@MFI]]> 37 98 3 <![CDATA[Zn5-Na2@MFI]]> 38 99 4 <![CDATA[Zn 10 -Na2@MFI]]> 38 98
[0083] It can be seen from the reaction results that high selectivity for acetaldehyde can be achieved when the Zn loading is in the range of 0.01-0.1%.
[0084] The performance evaluation results of Zn-Na@MFI catalysts with different sodium loading amounts in Examples 1 and 5-7 are shown in Table 4.
[0085] Table 4 Performance evaluation results of Zn-Na@MFI catalysts with different sodium loadings
[0086] Example catalyst Ethanol conversion rate (%) Acetaldehyde selectivity (%) 1 Zn1-Na2@MFI 36 100 5 <![CDATA[Zn1-Na4@MFI]]> 33 100 6 <![CDATA[Zn1-Na 10 @MFI]]> 32 100 7 <![CDATA[Zn1-Na 20 @MFI]]> 30 100
[0087] It can be seen from the reaction results that a high selectivity of 100% for acetaldehyde can be achieved when the sodium loading is in the range of 0.2-2%.
[0088] The performance evaluation results of the Zn-Na@MFI catalysts at different calcination temperatures of Examples 1 and 8-11 are shown in Table 5.
[0089] Table 5 Catalytic performance evaluation results of single-atom Zn-Na@MFI molecular sieve catalyst at different calcination temperatures
[0090] Example Calcination temperature (℃) Ethanol conversion rate (%) Acetaldehyde selectivity (%) 1 550 36 100 8 350 30 97 9 450 33 99 10 650 45 98 11 750 47 96
[0091] It can be seen from the table that the catalyst provided by the present invention can stably exist and produce the target product acetaldehyde under the condition of calcination temperature of 350-750°C, and the optimal calcination temperature of the reaction is 550°C.
[0092] In order to further highlight the superiority of the present invention, the reaction performances of Zn-Na@MFI catalysts modified with different base centers in Example 1 and Comparative Examples 3-5 were compared, and the performance evaluation results are shown in Table 6.
[0093] Table 6 Performance evaluation results of single-atom Zn-M@MFI molecular sieve catalysts modified with different base centers
[0094] Group Ethanol conversion rate (%) Acetaldehyde selectivity (%) Example 1 36 100 Comparative Example 3 10 70 Comparative Example 4 8 68 Comparative Example 5 5 73
[0095] The above results indicate that only the Na-modified zeolite catalyst can achieve high selectivity and high conversion of acetaldehyde.
[0096] Compared with the nanocatalyst Zn nano -Na@MFI and the reaction performance of single atom catalyst Zn-Na@MFI. The performance evaluation results are shown in Table 7.
[0097] Table 7 Performance evaluation results of nanocatalysts and single-atom catalysts
[0098] Group Ethanol conversion rate (%) Acetaldehyde selectivity (%) Example 1 36 100 Comparative Example 2 13 79
[0099] From the reaction, it can be seen that compared with the nanocatalyst, the single-atom catalyst has significantly higher ethanol activity and acetaldehyde selectivity.
[0100] In order to further highlight the uniqueness of the present invention, the reaction performances of Na-modified single-atom catalysts (Na / Zn@MFI and Na-Zn@MFI) synthesized in different ways, as well as Zn@MFI single-atom catalysts without Na modification and Zn-Na@MFI single-atom catalysts are compared to further highlight the superiority of the catalyst of the present invention and prove that the effect of the present invention is unpredictable. The performance evaluation results are shown in Table 8.
[0101] Table 8 Performance evaluation results of Na-modified single-atom catalysts synthesized by different methods
[0102] Group Ethanol conversion rate (%) Acetaldehyde selectivity (%) Example 1 36 100 Comparative Example 1 16 72 Comparative Example 6 13 83 Comparative Example 7 15 82
[0103] It can be seen from the above table that compared with the sodium modification process in the hydrothermal synthesis process, the sodium modification process without sodium modification of the catalyst, the impregnation method and the ion exchange method cannot achieve high selectivity for acetaldehyde and high activity for ethanol. This result once again confirms the uniqueness of the present invention.
[0104] Application Example 2
[0105] 1 g of the catalyst prepared in Example 1 was pelletized and loaded into a fixed bed reactor. The ethanol flow rate was 0.02 ml / min. The raw materials were brought into the reactor by pump feeding and nitrogen carrier gas (flow rate was 100 mL / min). The reaction space velocity was WHSV=1 h -1 The catalytic performance was investigated at different reaction temperatures.
[0106] Table 9 Catalytic performance evaluation results of single-atom Zn-Na@MFI molecular sieve catalyst at different reaction temperatures
[0107] Reaction temperature (℃) Ethanol conversion rate (%) Acetaldehyde selectivity (%) 250 18 100 275 27 100 300 36 100 325 45 100 350 47 98 375 53 97 400 69 95
[0108] It can be seen from the table that the catalyst provided by the present invention can produce the target product acetaldehyde under the reaction conditions of 250-400°C.
[0109] Application Example 3
[0110] 1 g of the single-atom Zn-Na@MFI molecular sieve catalyst prepared in Example 1 was pelletized and loaded into a fixed bed reactor. The ethanol flow rate was 0.02 ml / min. The raw materials were brought into the reactor by pump feeding and nitrogen carrier gas (flow rate was 100 mL / min). The reaction space velocity was WHSV=1 h -1 The reaction temperature was 300 °C for stability evaluation.
[0111] from Figure 4 It can be seen that the catalyst can operate stably for more than 300 h, and its reaction stability is higher than that of the currently reported Zn-based catalysts, indicating that the present invention has superiority.
[0112] like Figure 1 The XRD characterization results show that the catalyst has an MFI topological structure and no characteristic peak of Zn oxide appears, indicating that Zn in the catalyst is highly dispersed.
[0113] like Figure 2 The physical adsorption characterization results show that the catalyst has a multi-level pore structure, confirming the effectiveness of the present invention.
[0114] In order to further reveal the effectiveness and innovation of base center modification, the particle size distribution of Zn nanoparticles before and after the reaction of Zn-Na@MFI catalyst was investigated by HRTEM, such as Figure 3 The electron microscopy results show that the active components of the Zn-Na@MFI catalyst are all dispersed at the atomic level, indicating the effectiveness of the present invention in preparing the single-atom metal molecular sieve catalyst. In addition, the Zn particles of the catalyst after the reaction did not agglomerate, which is also a major innovation of the present invention.
[0115] In summary, the present invention uses a base-centered Na-modified Zn@MFI molecular sieve single-atom catalyst, which can be used for the non-oxidative dehydrogenation of ethanol to produce acetaldehyde. The catalyst prepared by this strategy has the advantages of good activity, high acetaldehyde selectivity, 100% Zn atomic utilization, and good reaction cycle stability.
[0116] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A Na-modified Zn@MFI molecular sieve single-atom catalyst, characterized in that: The catalyst is represented by the formula Zn-Na@MFI, wherein Zn and Na are active components, MFI molecular sieve carrier, Zn is dispersed in the MFI molecular sieve carrier in the form of single atoms, and the loading amounts of active components Zn and Na element in the catalyst are 0.1-1wt% and 0.2-2wt% respectively.
2. The catalyst according to claim 1, characterized in that: The loading amount of Zn element in the catalyst is 0.01-0.2wt%; the loading amount of Na element in the catalyst is 0.02-0.5wt%.
3. A method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: (1) mixing a silicon source, a template, a ligand protective agent, a sodium source, a zinc source and water, controlling the pH value to be 9-13, and stirring for 1-5 hours to obtain a gel; (2) subjecting the gel obtained in step (1) to a hydrothermal crystallization reaction; (3) After the hydrothermal crystallization is completed, centrifugation is performed, and drying is performed under vacuum conditions, followed by reduction calcination in a hydrogen atmosphere. The reduction calcination temperature is 350-750° C. and the calcination time is 2-6 h to obtain the catalyst.
4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of the silicon source, the template, the ligand protective agent, the sodium source, the zinc source and water is 1:2-5:0.02-0.1:0.001-0.02:0.001-0.01:20-50.
5. The preparation method according to claim 3, characterized in that: In step (1), the silicon source is one or both of tetraethyl orthosilicate and silica sol; The sodium source is one or more of sodium nitrate, sodium hydroxide, sodium chloride, sodium benzoate and sodium carbonate; The zinc source is one or more of zinc nitrate, zinc chloride, zinc acetylacetonate and zinc acetate; The template agent is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide; The ligand protecting agent is one or more of ethylenediamine, ethylenediaminetetraacetic acid and dopamine.
6. The preparation method according to claim 3, characterized in that: In step (2), the hydrothermal crystallization temperature is 100-200° C. and the time is 36-120 h.
7. The preparation method according to claim 3, characterized in that: In step (2) and step (3), the drying temperature is 50-120° C., and the hydrogen flow rate is 10-100 ml / min.
8. Use of the catalyst according to any one of claims 1 to 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 7 in the non-oxidative dehydrogenation of ethanol to produce acetaldehyde, characterized in that: The reaction is carried out in a fixed bed reactor, the ethanol feed rate is 0.005-1 ml / min, and the reaction mass space velocity is WHSV=0.5-10 h -1 At least one of argon, nitrogen and helium is used as carrier gas, the carrier gas flow rate is 40-200 mL / min, and the reaction temperature is 150-400°C.
Citation Information
Patent Citations
Synthesis method of 1,3-butadiene and preparation method of catalyst
CN109894144A
Catalyst for reaction for preparing 1,3-butadiene from ethanol, preparation and applications thereof
CN111217656A
In-situ preparation method of high-stability molecular sieve supported metal catalyst
CN113751055A
Large-grain Zn-coated Silicalite-1 light alkane dehydrogenation catalyst and preparation method thereof
CN115805097A
Cited By
Integrated process for preparing acetaldehyde from oxalate
CN121044958A